2014
DOI: 10.1371/journal.pone.0113493
|View full text |Cite
|
Sign up to set email alerts
|

Differential Interaction Kinetics of a Bipolar Structure-Specific Endonuclease with DNA Flaps Revealed by Single-Molecule Imaging

Abstract: As DNA repair enzymes are essential for preserving genome integrity, understanding their substrate interaction dynamics and the regulation of their catalytic mechanisms is crucial. Using single-molecule imaging, we investigated the association and dissociation kinetics of the bipolar endonuclease NucS from Pyrococcus abyssi (Pab) on 5′ and 3′-flap structures under various experimental conditions. We show that association of the PabNucS with ssDNA flaps is largely controlled by diffusion in the NucS-DNA energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…NucS was reported to be a bipolar nuclease acting on branched DNAs, including flapped and splayed DNAs ( 27 ). Furthermore, extensive structural analyses of this protein have been published ( 30 , 31 ). Therefore, we tested the branched DNAs, as well as the mismatched DNAs, as substrates for TkoEndoMS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NucS was reported to be a bipolar nuclease acting on branched DNAs, including flapped and splayed DNAs ( 27 ). Furthermore, extensive structural analyses of this protein have been published ( 30 , 31 ). Therefore, we tested the branched DNAs, as well as the mismatched DNAs, as substrates for TkoEndoMS.…”
Section: Resultsmentioning
confidence: 99%
“…Proliferating cell nuclear antigen (PCNA) is a well-known clamp molecule that provides a scaffold for many proteins functioning in DNA replication and repair ( 35 , 36 ). Pyrococcus abyssi NucS reportedly interacts with its cognate PCNA ( 27 , 30 , 31 ). The putative PCNA-binding sequence in TkoEndoMS is QKTLF, at the C terminus (Supplementary Figure S1), and it seems to be a short version of the PIP ( P CNA I nteracting P rotein) box ( 37 ).…”
Section: Resultsmentioning
confidence: 99%
“…To identify potential MMR enzymes in species apparently lacking MutL/MutS, cosmid-expressed Pyrococcus furiosus genome regions were screened for the ability to cleave the DNA backbone at the site of mismatches and resulted in the isolation of NucS/EndoMS [78]. NucS (later aliased EndoMS) constitutes a novel family of archaeal and bacterial endonucleases originally identified when bioinformatically screening the genome of Pyrococcus abyssii for an amino acid motif known to bind the replication clamp PCNA [79]. Initially, NucS/EndoMS was investigated for activity upon branched structures which arise due to DNA damage or as a replication intermediate, but not for recognition of mismatched bases [80].…”
Section: Nucs/endomsmentioning
confidence: 99%
“…The cleavage of flapped and splayed DNA substrates by Pab NucS suggests that this endonuclease is a potential archaeal NER endonuclease that can remove helix-distorting DNA damages ( Rouillon and White, 2011 ). Furthermore, Rezgui et al (2014) revealed that NucS endonuclease is a bipolar structure-specific endonuclease. In vivo , the engineered NucS-knockout strains of S. acidocaldarius are sensitive to DNA adducts, however, they did not show higher mutation rates ( Suzuki and Kurosawa, 2019 ).…”
Section: Archaeal Nucs Endonucleases In Nucleotide Excision Repairmentioning
confidence: 99%